Best jobs for the 21st century [ - Shatkin, Laurence (JIST's best jobs series, 2012)
400 job descriptions, ranked by earnings, growth through 2018, annual openings, etc.; also includes 69 best jobs lists organized by earnings, education, personality type, self-employment, growth, interests, age, gender, etc.